DETERMINATION OF THE BINDING PARAMETERS OF THE ADDUCT 3-NITRO PHENYLFERROCENE-DNA USING CYCLIC VOLTAMETRY, ELECTRONIC SPECTROSCOPY AND MOLECULAR DOCKING SIMULATION - Ben amara, H.; Lanez, Touhami (Journal of Fundamental and Applied Sciences, 2019)
Binding parameters of the interaction of 3-Nitrophenylferrocene (3FcNO2) with DNA, has been measured by cyclic voltametry (CV) and electronic spectroscopy (Uv-Vis). The obtained results were validated by molecular docking (MD) using AutoDock Tools software. CV results further indicated that 3FcNO2 interact to DNA by hydrogen bonding with binding constant and binding free energy values equal to 7.59×104 M−1 and −27.85 KJ.mol-1 respectively. These values were in a good agreement with those obtained from Uv-Vis measurements. The diffusion coefficient values of the free and bounded 3FcNO2 with DNA obtained from CV experiments were respectively equal to 9.71×10-8 and 4.33×10-9, this finding further confirm the formation of 3FcNO2-DNA adduct. Binding parameters were also estimated by MD, the obtained values were identical to experimental results.